2021
DOI: 10.3389/fmed.2021.750170
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Synergistic Antitumor Effect of a Borneol-Modified Nanocarrier Drug Delivery System

Abstract: Borneol, a traditional Chinese medicine, can enhance therapeutic efficacy by guiding the active ingredients to the target site. Reportedly, borneol improves the penetration capacity of the nasal, cornea, transdermal, intestinal, and blood-brain barriers. Although nanotechnology dramatically changed the face of oncology by targeting tumor sites, the efficiency of nanoparticles delivered to tumor sites is very low, with only 0.7% of the total particles delivered. Thus, based on the penetration ability and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Borneol, an alkaloid compound naturally present in the plant borneol (Borneolum Syntheticum), is a commonly used component in Chinese herbal medicine. Research conducted by Li et al [51] in 2021 on nanocarriers modified with borneol revealed that borneol can improve therapeutic efficacy, reduce toxicity, inhibit tumor metastasis, and reverse multidrug resistance. Moreover, berberine, an isoquinoline alkaloid isolated from Coptis chinensis (Coptis chinensis), was also widely explored as a potential natural anticancer therapeutic agent [52].…”
Section: Alkaloid Compoundsmentioning
confidence: 99%
“…Borneol, an alkaloid compound naturally present in the plant borneol (Borneolum Syntheticum), is a commonly used component in Chinese herbal medicine. Research conducted by Li et al [51] in 2021 on nanocarriers modified with borneol revealed that borneol can improve therapeutic efficacy, reduce toxicity, inhibit tumor metastasis, and reverse multidrug resistance. Moreover, berberine, an isoquinoline alkaloid isolated from Coptis chinensis (Coptis chinensis), was also widely explored as a potential natural anticancer therapeutic agent [52].…”
Section: Alkaloid Compoundsmentioning
confidence: 99%
“…Generally, they are hydrophobic, which means low water solubility. Borneol , a bicyclic monoterpene, isolated from Dryobalanops aromatica Gaertn f. and Blumea balsamifera DC , has been used as a messenger drug encapsulated in liposomes to help other drugs penetrate physiological barriers, such as blood-brain barrier ( Zhang et al, 2020 ; Li et al, 2021d ). Galactosylated-stearate (Gal-s) modified liposome enhanced the targeted delivery of curcumol and the treatment of liver cancer cells ( Li et al, 2018a ).…”
Section: Construction Of Liposomal Systems For Medicinal Natural Prod...mentioning
confidence: 99%
“…The effect of enhanced curcumin uptake by the cells pretreated with borneol could be due to the low molecular weight and high lipophilicity of this monoterpene. However, other mechanisms, such as loosening of tight junctions and the loss of mucous viscosity and elasticity have also been proposed to explain its drug penetration enhancing effect [75,76].…”
Section: Borneol and Its Estersmentioning
confidence: 99%